BIOCHEMICAL CHANGES IN PATIENTS UNDERGOES THYROID SURGERY (World Bulletin of Public Health, 2023)
Once death from thyroid operation became an exception, specific pitfalls of the procedure, namely, injuries to the laryngeal nerves and damage to the parathyroid glands became obvious. Halsted is credited for his studies of surgical anatomy and blood supply of the parathyroid glands and the introduction of the technique of capsular dissection that implemented preservation of the vascular pedicle of a parathyroid gland and led to a safer approach to thyroid and parathyroid surgery. Today morbidity remains a subject of concern for surgeons performing thyroid and parathyroid procedures. Injury of the recurrent laryngeal nerve and hypoparathyroidism are the most frequent complications.